2005
DOI: 10.1200/jco.2005.02.191
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Smac/DIABLO Expression in Renal Cell Carcinoma and Its Prognostic Significance

Abstract: The present study demonstrates for the first time that Smac/DIABLO expression was downregulated in RCC and that no Smac/DIABLO expression in RCC predicted a worse prognosis. In addition, transfection with Smac/DIABLO sensitized RCC to TRAIL/cisplatin-induced apoptosis. These results suggest that Smac/DIABLO expression in RCC may be used as a prognostic parameter, and that enhancement of Smac/DIABLO expression in RCC may potentiate immunotherapy and chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 21 publications
9
66
0
2
Order By: Relevance
“…Smac/DIABLO accelerates XIAP autoubiquitination and self degradation and modulates protein expression levels. Noteworthy, we have recently reported in RCC that the expression of Smac/DIABLO is significantly decreased and is an independent prognostic factor for RCC (21). Thus, it is possible that the down-regulation of Smac/ DIABLO contributed, in large part, to the stabilization and high level of XIAP expression in RCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smac/DIABLO accelerates XIAP autoubiquitination and self degradation and modulates protein expression levels. Noteworthy, we have recently reported in RCC that the expression of Smac/DIABLO is significantly decreased and is an independent prognostic factor for RCC (21). Thus, it is possible that the down-regulation of Smac/ DIABLO contributed, in large part, to the stabilization and high level of XIAP expression in RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Smac/DIABLO binds to XIAP, displaces XIAP from caspase-9, promotes cleavage of effector caspases, and induces apoptosis (6,39). In addition, our previous study demonstrated that Smac/DIABLO expression was downregulated in RCC, and that no Smac/DIABLO expression in RCC predicted a worse prognosis (21). Therefore, the measurement of Smac/DIABLO expression as well as XIAP expression may be necessary for an accurate prediction of prognosis in RCC patients and an accurate evaluation of the efficacy of the therapy using XIAP antagonists in combination with immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, downregulation of the mitochondrial IAP antagonist Smac/DIABLO is associated with renal cell carcinomas, and overexpression of survivin, another IAP, has been observed in most transformed cell lines and cancers tested to date, as compared with its absence in most normal adult tissues. 12,13 Although there is evidence suggesting an indirect caspase-9 processing interference by survivin, 14 malfunctions of mitotic spindle checkpoint and aberrant progression of transformed cells may be due to non-apoptotic functions of this particular IAP. 15 Association between X-linked inhibitor of apoptosis protein (XIAP) overexpression and poor clinical outcome has been reported for both renal cell carcinomas and acute myelogenous leukemia (AML).…”
Section: Apoptosis As a Defense Strategy Against Tumorogenesismentioning
confidence: 99%
“…Note Smac protein expression is downregulated in RCC and no expression of Smac predicts a worse prognosis (Mizutani et al, 2005). Either Smac mRNA expression is inversely associated with outcome of RCC patients (Kempkensteffen et al, 2008a).…”
Section: Renal Cell Carcinomamentioning
confidence: 99%